2000
DOI: 10.1076/clin.14.4.535.7198
|View full text |Cite
|
Sign up to set email alerts
|

Myths of Neuropsychology: Intelligence, Neurometabolism, and Cognitive Ability

Abstract: Recently, Dodrill (1999) revised a previously described "Myth of neuropsychology" (1997) to state: "Just as below average performances on neuropsychological tests are found when intelligence is below average, to that same degree above average performances on neuropsychological tests are expected when intellectual abilities are above average." This study addresses the relationship between intellectual and neuropsychological performance in the context of Magnetic Resonance Spectroscopy (MRS) measurements of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 33 publications
2
32
0
1
Order By: Relevance
“…Previous studies (mainly in adults or adolescents) have shown various neuropsychological functions to be substantially related to general intelligence (DiazAsper, Schretlen, & Pearlson, 2004;Jung, Yeo, Chiulli, Sibbitt, & Brooks, 2000;Seidenberg, Giordani, Berent, & Boll, 1983). However, results are mixed with regard to the strength of the association for different neuropsychological domains, and multiple studies have pointed out that not all different neuropsychological functions can be explained equally well by intelligence.…”
Section: Introductionmentioning
confidence: 79%
“…Previous studies (mainly in adults or adolescents) have shown various neuropsychological functions to be substantially related to general intelligence (DiazAsper, Schretlen, & Pearlson, 2004;Jung, Yeo, Chiulli, Sibbitt, & Brooks, 2000;Seidenberg, Giordani, Berent, & Boll, 1983). However, results are mixed with regard to the strength of the association for different neuropsychological domains, and multiple studies have pointed out that not all different neuropsychological functions can be explained equally well by intelligence.…”
Section: Introductionmentioning
confidence: 79%
“…The issue of neuropsychological test performance among individuals with above average IQ has been the topic of some controversy (Jung, Yeo, Chiulli, Sibbitt, & Brooks, 2000;Russell, 2001;Tremont, Hoffman, Scott, & Adams, 1998). Dodrill (1997Dodrill ( , 1999 observed that while IQ scores below the average range are often correlated with a variety of neuropsychological measures, the same relationship does not hold true for individuals with average to above average IQ.…”
mentioning
confidence: 97%
“…Previously it has been used to correlate low-level sensory discriminations with intelligence (Melnick and Harrison et al, 2013), developmental cognitive abilities with task performance (Pangelinan and Zhang et al, 2011;Smits-Engelsman and Hill, 2012), and neural correlates of specific cognitive abilities (Margolis and Bansal et al, 2013). It is also suggested that the cognitive motor abilities and intelligence may share the same neural substrates (Jung and Yeo et al, 2000;Duncan, 2005;Stevens, 2009). Similarly, functional studies support the idea of distributed networks in the brain and suggest that intelligent brains process information more efficiently during a cognitive task (Achard and Salvador et al, 2006;Jung and Haier, 2007;van den Heuvel and Stam et al, 2009).…”
Section: Introductionmentioning
confidence: 92%
“…Many studies on the neuroscience of intelligence or on differential psychology have tried to identify the fundamental parameters of cognitive processing or the functional and biological variables that account for inter-individual intelligence differences. Psychometric tests of intelligence evaluate cognitive domains such as reasoning, processing speed, executive function, memory, and spatial ability (Wechsler, 1981;Jung and Yeo et al, 2000;Colom and Abad et al, 2002;Raven and Raven, 2003;MacDonald and Nyberg et al, 2006). The intelligence quotient (IQ) tends to remain relatively stable across development (Deary and Whalley et al, 2000;McArdle and Ferrer-Caja et al, 2002) and the estimation of IQ by means of psychometric tests is an index of relative intelligence that measures how well an individual performs in a cognitive domain with respect to a reference group of the same age.…”
Section: Introductionmentioning
confidence: 99%